Chemical and biological activities of faveleira (Cnidoscolus quercifolius Pohl) seed oil for potential health applications. (1st February 2021) - Ribeiro, Penha Patrícia Cabral; Damasceno, Karla Suzanne Florentino da Silva Chaves; de Veras, Bruno Oliveira; de Oliveira, João Ricardhis Saturnino; Lima, Vera Lúcia de Menezes; de Assis, Caio Rodrigo Dias; da Silva, Marcia Vanusa; de Sousa Júnior, Francisco Canindé; de Assis, Cristiane Fernandes; Padilha, Carlos Eduardo de Araújo; Stamford, Thayza Christina Montenegro
Highlights: The seed oil of faveleira has potential to be used as a functional edible oil. This oil is rich in essential fatty acids and bioactive molecules. The oil under study presented antioxidant activity, oxidative and thermal stability. The faveleira oil showed no toxicity in vitro and in vivo . The faveleira seed oil presented anti-inflammatory and antinociceptive activities. Abstract: Faveleira ( Cnidoscolus quercifolius ) is an emerging Brazilian plant, with seeds rich in edible oil. This study investigates physicochemical properties, chemical composition, thermal and oxidative stability, in vitro and in vivo toxicity, antioxidant, antinociceptive and anti-inflammatory activities of faveleira seed oil. It was observed that the oil has low acidity, value of peroxide, chlorophyll, carotenoids, β-carotene and high concentrations of unsaturated fatty acids. In addition to presenting thermal and oxidative stability and high total phenolic content, with vanillin, eugenol and quercetin were predominating. The oil showed no toxicity in vitro and in vivo, and presented antioxidant, anti-inflammatory and antinociceptive activities. These findings provide relevant and appropriate conditions for processing of faveleira seed oil as functional food.